2017
DOI: 10.3892/mmr.2017.6440
|View full text |Cite
|
Sign up to set email alerts
|

Removal from adherent culture contributes to apoptosis in human bone marrow mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) are routinely isolated due to their adherence to tissue culture plates and their in vitro growth characteristics. Expansion of MSCs in adherent cultures is the only way to obtain sufficient cells for use in either clinical or research settings. MSCs have tremendous potential in myocardial repair treatment by cell therapy techniques, however, a large number of MSCs die from apoptosis following transplantation. Previous studies have examined the factors contributing to the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Indeed, in our immunohistological staining of actin using phalloidin, we found that cells were distributed along the residual gelatin of vhEGCG-GSs at 4 weeks, and sporadic cells were present at bone defect areas in the vhGS group. The attached cells, similar to osteoblasts and multipotent progenitor cells associated with bone formation, require robust cell attachment for survival [33,34]. Rapid digestion of gelatin by MMP-2 and -9 could yield a fragile, brittle scaffold for cell attachment and prevent bone formation by vhGSs, whereas vhEGCG-GSs seemed to provide a sufficient scaffold for cells via the inhibitory effects of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in our immunohistological staining of actin using phalloidin, we found that cells were distributed along the residual gelatin of vhEGCG-GSs at 4 weeks, and sporadic cells were present at bone defect areas in the vhGS group. The attached cells, similar to osteoblasts and multipotent progenitor cells associated with bone formation, require robust cell attachment for survival [33,34]. Rapid digestion of gelatin by MMP-2 and -9 could yield a fragile, brittle scaffold for cell attachment and prevent bone formation by vhGSs, whereas vhEGCG-GSs seemed to provide a sufficient scaffold for cells via the inhibitory effects of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…We set up an innovative NMP perfusion system coupled with a MSCs-bioreactor with the aim to improve the application of cell-based therapies during NMP while avoiding any potential drawback related to stem cell direct administration 18,[32][33][34][35][36] . The particular con guration of our platform allowed a bidirectional communication between the liver and MSCs, enabling the cells to be primed with the perfusate enriched by the molecules secreted from the hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell cryopreservation itself can further reduce survival and trigger oxidative stress 32 . In addition, since MSCs are typically plastic-adherent in vitro, keeping these cells in suspension lead to apoptosis activation 33 . Direct cell administration and their migration into the graft raise other important concerns related to the risk of microvascular embolism 34,35 and unintended dedifferentiation of MSCs 36 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ROS can initiate chain reactions, and react with a variety of unsaturated fatty acids and cholesterol on the cell membrane, resulting in oxidative damage to cells and eventually apoptosis. Cell death via apoptosis serves a role in maintaining normal tissue morphology and cell death, which are under the control of apoptosis-associated genes ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%